2005
DOI: 10.1016/j.amjhyper.2004.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Correlates of Serum Aldosterone in the Community: The Framingham Heart Study

Abstract: We observed a complex relation between serum aldosterone and vascular risk factors. The genetic contribution to serum aldosterone level was modest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
2
6

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 47 publications
8
60
2
6
Order By: Relevance
“…Concordant with many studies [19,31,32], our study demonstrated a positive correlation between PA levels and s.triglycerides and a negative correlation between PA levels and high-density lipoprotein (HDL) cholesterol. Some authers [19] demonstrated that patients with the highest aldosterone levels showed the lowest HDL levels.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Concordant with many studies [19,31,32], our study demonstrated a positive correlation between PA levels and s.triglycerides and a negative correlation between PA levels and high-density lipoprotein (HDL) cholesterol. Some authers [19] demonstrated that patients with the highest aldosterone levels showed the lowest HDL levels.…”
Section: Discussionsupporting
confidence: 79%
“…Bochud et al, [31] showed a negative association between plasma aldosterone levels and HDL cholesterol levels in MSyn patients, regardless of all of the other MSyn components. However, a Framingham Heart Study subanalysis with higher subject numbers (2891subjects) did not show a direct correlation between aldosterone and low HDL cholesterol [32]. Therefore, a possible causative relation between aldosterone and lipid metabolism needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Studying normotensive monozygotic and dizygotic twins gave no evidence of a genetic influence on plasma aldosterone concentration; urinary excretion of aldosterone, on the other hand, was clearly heritable in another study . In contrast, plasma aldosterone in the Framingham offspring population was only modestly heritable (h 2 =0.1, p<0.04) (Kathiresan et al 2005); this was confirmed in a study of 43 hypertensive sibling pairs (h 2 =0.19) (Kotchen et al 2000). It was clear from these studies that short-term environmental changes in dietary salt, potassium and posture could obscure the true heritability of aldosterone, as determined by single plasma aldosterone samples.…”
Section: Genetic Determination Of Aldosterone Levelsmentioning
confidence: 62%
“…Despite being a highly heritable characteristic, this study showed that polymorphic variation in CYP11B2 and CYP11B1 only accounts for up to 10% of the observed variability in THaldo excretion. Furthermore, a subsequent study could not identify any association between plasma aldosterone levels and polymorphic variation in the CYP11B2 and mineralocorticoid receptor (MR) genes (Kathiresan et al 2005). Therefore, it is clear that other genetic factors, such as those encoding other components of the Renin Angiotensin System (RAS), must…”
Section: The Cyp11b1/cyp11b2 Locus In Essential Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation